SOCIAL SECURITY IN DEVELOPING COUNTRIES: MYTH OR NECESSITY? EVIDENCE FROM INDIA - PATRICIA JUSTINO (PRUS WORKING PAPER NO. 20, 2003)
This paper discusses the importance of social security policies in developing economies, using empirical evidence from India. The paper discusses the viability of implementing systems of social protection in developing countries and provides an empirical analysis of the effects of socio-economic security policies on Indian's economic performance between 1973 and 1999, using a two-stage least square model adapted to data from a panel of 14 Indian states. The results show that policies that strengthen the social and economic security of the Indian population have been an important endogenous variable to both the reduction of poverty and the economic growth in India.